Checking up on Y2K. - Perry, T.S.
The author describes how, with critical industries worldwide spending hundreds of billions on Y2K remedies, the ultimate test has yet to come, but intermediate trials foretell less of a plague than a head cold
Keywords: Millennium bug; Y2K.; Critical industries; Intermediate trials; Public utilities